The Nature of the Virtuous Soul in al-Ghazali and Hamka - Megawati Bt Moris; Muhammad Nurrosyid Huda Setiawan (Universitas Darussalam Gontor, 2019)
This paper elaborates view of al-Ghazali and Hamka on the healthy soul in ‎tasawwuf. Both have an interest correlation in understanding healthy soul with different ‎ways of explanation. Hamka affirmed that healthy soul should be maintained by four ‎qualities; syaja>’ah, ‘iffah, hikmah, and ‘ada>lah. In fact, these four qualities are known as ‎ummaha>t al-fada>il or the mother of virtuous in the book of al-Ghazali. Al-Ghazali’s way in ‎explaining the meaning of ummaha>t al-fada>il, however, is different with Hamka, making this ‎issue is important to be discussed. This research is done using descriptive analysis method ‎to elaborate both al-Ghazali and Hamka’s idea on healthy soul, before finally compared ‎in order to gain multiple results based on their different perspectives on this issue. ‎Researcher finds afterwards that Hamka was much influenced by al-Ghazali’s thought, but ‎attractively, Hamka succeeded to contextualize thea meaning of healthy soul in accordance ‎with al-Ghazali’s thought into Indonesian context in a more simple way to be understood ‎by all people, especially in the land of archipelago.‎